Interactive MOLP explorer-A graphical-based computational tool for teaching and decision support in multi-objective linear programming models - Alves, Maria João; Antunes, Carlos Henggeler; Clímaco, João (Computer applications in engineering education, 2015)
ABSTRACT This article presents an interactive computational tool for teaching and providing decision support in multi‐objective linear programming models. The main aim is to offer students in engineering and economics & management a user‐friendly environment where the main theoretical and methodological concepts of multi‐objective optimization can be apprehended through experimentation. © 2014 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:314–326, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21601